Shift Work as a Predictor of Fatigue Levels Among Inpatient Nurses: A Cross-Sectional Analysis - Mahardika, I Ketut Diva; Yuliani, Eka; Nela, Ari Sukma (Inspirasi Foundation, 2025)
Intorduction: Hospitals operate continuously to provide essential healthcare services, relying heavily on nurses who often work rotating shifts. These shift patterns, particularly night shifts, can lead to fatigue, which negatively impacts nurses’ health, performance, and patient safety. Objective: This study aimed to analyze the relationship between work shifts and nurse fatigue in the inpatient department of Dr. A. Dadi Tjokrodipo Hospital in 2024. Method: A quantitative analytical survey with a cross-sectional design was conducted. The study population included all inpatient nurses, with a total of 57 respondents selected using total sampling. Data were collected using validated questionnaires and analyzed using Chi-Square tests to determine associations. Result: The findings revealed that nurses working under shift schedules were more likely to experience fatigue compared to those on regular schedules. The statistical analysis demonstrated a significant association between shift work and nurse fatigue (p < 0.05). Conclusion: Shift work is significantly associated with increased nurse fatigue. Hospital administrators should consider implementing better shift management strategies to reduce fatigue and improve both nurse well-being and the quality of patient care.